(untitled) (Medical Forum Monthly, 2024)
Objective: Pharmacological studies of vitamin E and vitamin C as antioxidants in patients with Parkinson’s disease. Design of study: Randomized, comparative and categorical study. Place and Duration of Study: This study was conducted in the Department of Pharmocology, Faculty of Pharmacy, University of Karachi in collaboration with Jinnah Post Graduate Medical College Hospital and Mamji Hospital from April 11, 2010 to August, 2010. Materials and Methods: On enrollment each patient received complete physical examination and laboratory tests were performed. All registered patients were advised to attend the respective outpatient department (OPDs) every week and at the end of 3rd month at a special counter allocated for the purpose of this study. Evaluation of the subjects was done on Patients Health Questionnaire and Unified Parkinson’s disease Rating Scale (UPDRS). Results: Patients responded to this combination in a very energizing way making them more active, less depressed and motivated. In some patients who were younger around age of 43 (as compared to others < 65 years) diseases free period duration increased to two folds. Some male patients found this combination very aphrodisiac Statistical analysis confirms the promising future of Antioxidants in patients with Parkinson’s disease (PD). Conclusion: Antioxidants in combination must be given to Parkinson’s patients in order to improve the quality of life. Especially at the early stages of Parkinson’s disease worsening of symptoms can be prevented or prolonged